Drama, creativity and thinking skills: the lost art of 'whole group drama' - Gears, Anthony (2003)
My primary aim in this research has been to present a case for the impact of a 'Drama as Process' whole group improvisation model on creativity and thinking skills and to assess how it may be more successful in raising achievement in those areas than 'performance' and 'convention' styles of drama. The thesis identifies the elements of teaching and learning styles which may develop creativity and thinking skills most effectively and examines other key learning areas developed in the 'drama improvisation process' and, how these are best approached. Whole group drama is a form of narrative story exploration carried out for the benefit of the participants, and is not concerned with performance for an audience beyond the immediate group of actor-spectators. The thesis presents a theoretical argument, and examines practice in detail to test out the validity of the whole group model and to provide concrete examples of it in practice. This thesis constitutes an argument illuminated by empirical evidence drawn from practice including: observation of classes; teaching of classes; experiments in improvisation and thinking skills, where the number of changes of direction in thinking required by participants, within a given time were recorded; observation, transcribing and analysing of videoed Drama lessons; interviews of individuals and classes; completion of pro-forma questionnaires by pupils, ex-pupils and staff Creativity and thinking skills are central to the methodology of whole group improvisation, and operate throughout the process. Through observation and discussion with students, it became clear that operating in the improvisation model they could work at their own level, developing their creativity and thinking skills in the manner most appropriate to the individual and as their levels of confidence grew. The contextualisation of their knowledge and understanding in the drama was seen to enable them to use their ideas in a relevant and experiential manner, without the hindrance of feeling they were 'showing/performing' or that they needed to plan or rehearse presentation, developing their flexibility and ability to react imaginatively and creatively to situations and questions